Retired Government Officials On The Board Of Commissioners And Tax Aggressiveness In Indonesia - Riandoko, Riko; Aribowo, Irwan; Royani, Zulfa (Educoretax, 2021)
This study aims to determine the effect of retired government officials on board of commissioners on corporate tax aggressiveness. The presence of retired government officials on board of commissioners is assessed by categorizing companies into three groups: the company without any retired government officials on board of commissioners, the c[1]ompany with one retired government official on board of commissioners, and the company with more than one retired government officials on board of commissioners. Corporate tax aggressiveness is measured using effective tax rate (ETR). The analysis is conducted on 441 observation data generated using purposive sampling for all the listed company on the Indonesia Stock Exchange in the period of 2014 to 2016. The results reveal that relative to there being one retired government official on the board of commissioners, greater than one retired government official presence on the board of commisioners does not reduces corporate tax aggressiveness